Rural Resource Management for Sustainability of Fuel - Nirmal Kumar , Mukesh Kumar Singh, Anil Kumar Dohare, (Indian Journal of Extension Education, 2022)
In rural India, fuel wood, cowdung and crop waste are used as kitchen fuel. These fuels have low heat output per unit of fuel used and releases lot of gases harmful for human health. In earlier days, the people were using the charcoal obtained frompartial burnt wood at the end of routine cooking practices. Practice also existed to turn the powdery coal into balls for use as fuel in some parts of the country.At the same time, peoplewere using the hard stalk/ straw etc. as such to build a fire for cooking and heating bio-fuel accounts for 80% of their kitchen energy needs. In rural areas, one expert opinion suggests sufficient food in the forthcoming years but insufficient fuel to cook the food, as the rate of deforestation is very high in comparison to the forestation. Rural population living in the villages is unable to shift to commercial fuel due to their lowpurchasing power and limited availability of commercial fuels. Urban poor (25-30%urban populations) are also heavily dependent on bio fuel due to short supply of commercial fuel like kerosene and liquefied petroleumgas. Biogas and biomass (agro-waste) are efficient sources of non-conventional energy, which can be used for alternative fuel for cooking. In spite of various concerted efforts by the Government of India, the roots of biogas technology could not penetrate down to the countryside. Therefore at this juncture, it is essential to focus on different aspects of biogas technology users and non- users with some specific objectives. The sample of the study consisted 21 biogas adopters and 79 non- adopters. The finding of the study reveals thatmajority of the beneficiaries favoured the use of biogas technology, as it eliminates environmental pollution and diseases caused due to smoke and prevents harvesting of immature trees for want of firewood needs. On the other hand, users had some misconception too about the installation, operation, maintenance of the biogas plants. The awareness of the adopter regarding different practices recommended was varied from 23.81 per cent to 90.47 per cent. However, they did not follow adoption of the practices at par with awareness. Majority of the beneficiaries had received many fold advantages of biogas technology. The study revealed that considerable number of biogas users expressed problems like economic, social, personal, technical, operational, organizational and psychological. In the light of expression of themajor constraints, it is implied that there is necessity to attempt to minimize these problems as per the suggestion given by them. An attempt was also made to investigate the preferences and fuel utilization pattern as well as inhibiting factors in acceptance of non-adopters. It was found that firewood is themajor fuel used by non-adopters due to availability of firewood in ample quantity.However, 46.83 per cent unwilling non- adopters were poor and orthodox and motivating them to adopt the technology is a challenge to the extension workers. By and large, these unwilling non- adopters resemble with the laggard’s category in the adoption process.